Family roles and interpersonal competencies of young women from alcohol-dependent families - Sokolviak, Любов (Psychosomatic Medicine and General Practice, 2024)
The aim of this study is to examine the relationship between family roles and interpersonal competencies in women from alcoholic families. Additionally, the study aims to investigate potential differences in the intensity of family roles and levels of interpersonal competencies between young adult women from alcoholic families and women from non-alcoholic families. The research group consisted of 107 women aged 18 to 35, with 58 participants in the experimental group and 49 participants in the control group. The Family Roles Questionnaire (FRQ) was used to assess family roles, while the Interpersonal Competence Questionnaire (ICQ-R) was employed to measure interpersonal competencies. The findings indicate a significant relationship between family roles and interpersonal competencies in young adult women from alcoholic families. The study revealed that engaging in dysfunctional family roles is associated with lower levels of interpersonal competencies among women from these families. Furthermore, there are statistically significant differences between the experimental and control groups regarding these variables. Specifically, young adult women from alcoholic families exhibited higher levels of dysfunctional family roles and lower levels of interpersonal competencies compared to women from non-alcoholic families. The research presented in this article is of significant importance in a therapeutic context and can contribute to the development of effective therapeutic strategies for women from families affected by alcohol-related issues.